2006
DOI: 10.1080/01904160500476897
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Responses to True and Bicarbonate-Induced Iron Deficiency in Grapevine Genotypes

Abstract: Biochemical responses to direct or bicarbonate-induced iron (Fe) deficiency were compared in two Tunisian native grapevine varieties, Khamri (tolerant) and Balta4 (sensitive), and a tolerant rootstock, 140Ru.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 20 publications
5
22
0
4
Order By: Relevance
“…In contrast, the FCR activity was not affected by iron deficiency in the T. salsuginea plant. The induction of root FCR activity was correlated to the tolerance to Fe deficiency in several species, as it was reported for lettuce (Msilini et al, 2012), chickpea (Mahmoudi et al, 2005), grapevine (Ksouri et al, 2006) and medicago (M'sehli et al, 2009). Several lines of evidence support the role of PEP-carboxylase (PEPC) in the adaptation of plants to environmental changes.…”
Section: Discussionmentioning
confidence: 66%
“…In contrast, the FCR activity was not affected by iron deficiency in the T. salsuginea plant. The induction of root FCR activity was correlated to the tolerance to Fe deficiency in several species, as it was reported for lettuce (Msilini et al, 2012), chickpea (Mahmoudi et al, 2005), grapevine (Ksouri et al, 2006) and medicago (M'sehli et al, 2009). Several lines of evidence support the role of PEP-carboxylase (PEPC) in the adaptation of plants to environmental changes.…”
Section: Discussionmentioning
confidence: 66%
“…In another work, Bavaresco, Fraschini, & Perino (1993) compared the response of 140 Ruggeri and 101-14 rootstocks to iron chlorosis showing that the iron-efficient rootstock (140 Ruggeri) did not induce chlorosis when growing on the calcareous soil, while the opposite occurred with the iron-inefficient rootstock (101-14). Ksouri, M'rah, Gharsalli, & Lachaâl (2006) found that the high tolerance of 140 Ruggeri to Fe-chlorosis is partially due to its high root Fe(III)-reductase activity and the ability of this rootstock to release phenolic compounds in the medium (Ksouri et al, 2006). Currently this rootstock is largely employed in south Mediterranean and North Africa viticulture areas, characterized by lime soils and dry environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…En estudios anteriores, se observó que dentro de una misma especie, existen genotipos sensibles y tolerantes a la clorosis férrica, y que difieren en su capacidad para acidificar la rizosfera (Rabotti y Zocchi, 2006;Rabotti et al, 1995;Tagliavini et al, 1995;Wey et al, 1997;Vizzotto et al, 1999;Dell'Orto et al, 2000b;Ksouri et al, 2006;Donnini et al, 2009;Jelali et al, 2010a). En un estudio sobre cítricos, Treeby y Uren (1993) observaron que las especies más tolerantes a la clorosis disminuían el pH de la solución nutritiva en respuesta a la deficiencia de Fe, mientras que los menos tolerantes no tenían esta capacidad tan desarrollada.…”
Section: Discussionunclassified
“…Por otro lado, las altas temperaturas producen la degradación de fitosideróforos, lo cual afecta directamente a la absorción del Fe en plantas de estrategia II (Bergmann, 1992 , guisante (Jelali et al, 2010a), vid (Tagliavini et al, 1995;Dell'Orto et al, 2000a;Ksouri et al, 2006), kiwi (Vizzotto et al, 1999), melocotón (Gogorcena et al, 2004;Jiménez et al, 2008Jiménez et al, , 2011 y cítricos (Treeby y Uren, 1993;Manthey et al, 1994;Pestana et al, 2005;Castle et al, 2009). …”
Section: Factores Ambientalesunclassified
See 1 more Smart Citation